FREQUENCY AND STRUCTURE OF CONGENITAL MALFORMATIONS IN THE CITY OF NOVOKUZNETSK FOR THE PERIOD 2012-2021 - Полина Евгеньевна Салтыкова; Светлана Владимировна Шрамко; Екатерина Александровна Чубарь; Анна Егоровна Власенко (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - to study the patterns and patterns of congenital fetal malformations (CHD) in the city of Novokuznetsk for the period from 2012-2021. Materials and methods. The analysis was carried out on the basis of a retrospective analysis of archival data from the gynecological department of the City Clinical Hospital N 1 named after G.P. Kurbatov. To calculate the indicators, data on the number of women of fertile age in the south of Kuzbass was used. Descriptive statistics were calculated using the Clopper-Pearson method. To determine statistically significant changes in the structure of the HF, the Cochran-Armitage test was used. To analyze the trend in the dynamics of relative indicators, the Mann-Kendall test was changed. Results. Frequency of pregnancy terminations due to congenital malformation of the fetus for the period 2012-2021 was generally stable (p = 0.72). Changes in the structure of congenital malformations were established: the frequency of central nervous system defects increased 2,3 times (p = 0.001), the incidence of malformations of the facial bones decreased 2.7 times (p = 0.023), and the incidence of malformations of the musculoskeletal system decreased 3.7 times (p = 0.049) and there is a 1,3-fold decrease in the frequency of multiple malformations (p = 0.001). Conclusion. Frequency of pregnancy terminations (per 100 thousand women of fertile age) due to congenital malformation of the fetus in general for the analyzed period 2012-2021 was stable. The structure of congenital malformations was dominated by multiple malformations. The results of the analysis indicate an increase in the proportion of central nervous system defects in the total number of congenital malformations, and the prevalence of pregnancy terminations for this reason has also increased. At the same time, the number of pregnancy terminations due to malformations of the facial bones has decreased significantly.